Women’s sexuality – future directions - Lew-Starowicz, Zbigniew; Błażejewska, Anita; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2007)
This article provides a short review of what you could find in sexology journals about the epidemiology, psychology, biology and complex pathophysiologies of female sexual function in recent years. Nowadays, women feel much more comfortable in talking about their sexual concerns and they much more readily decide to seek help. The main reason for that is the increased discourse and awareness of the extent of women’s sexual dysfunctions. The latest conferences devoted to the definition and classification of female sexual dysfunctions have significantly influenced assessment and management.